Strategi Pembelajaran PAI Untuk Mempersiapkan Siswa Menghadapi Era Globalisasi - Diva Aufanisa; Roza Safitri; Dzakiratul Husna; Gusmaneli (Jurnal Kajian Islam dan Sosial Keagamaan, 2024)
In the era of globalization, it is crucial for students to be prepared with the necessary skills and knowledge to compete in the global job market. This article discusses the strategies for implementing PAI (Pendidikan Anak Indonesia) in Indonesian schools to prepare students for the challenges of globalization. The article outlines the importance of PAI, its objectives, and the challenges faced in its implementation. It also presents practical strategies to overcome these challenges and ensure the success of PAI in Indonesian schools. By implementing these strategies, schools can provide students with the necessary skills and knowledge to succeed in the global job market and contribute positively to society